Secagem convectiva de concentrado de minério de ferro: abordagem experimental e simulações por fluidodinâmica computacional - Souza, Amarílis Severino e (2023)
Conventional transfer chutes are equipment used to change the solids flow direction in transporting systems that use conveyor belts. During operation, the solid transported by the upper conveyor belt enters the chute and falls, from where it is directed to the lower conveyor belt, changing its flow direction. A patent from Vale S.A company describes the adaptation of the transfer chute as an industrial drying unit, consisting of feeding hot air in the base of the equipment, which rises and exchanges heat and mass with the falling wet ore. One of the main advantages of the adapted equipment is the implementation of a moisture reduction process for iron ore concentrates in an equipment already installed on the production line. However, since it is a new technology, many aspects of its operation are unknown. The objective of this work was to simulate by computational fluid dynamics (CFD) the operation of the drying chute, referring to a unit installed in the pelletizing plant of São Luís/MA, analyzing and evaluating the momentum, heat, and mass transport phenomena involved. It was decided to experimentally obtain a correlation for the mass transfer coefficient (K), which is a key simulating parameter to be implemented in the CFD simulations for greater precision in describing the iron ore drying rate. The procedure for obtaining and validating the correlation for K was initially executed in a laboratory-scale dryer called FB-2. Thin layer drying experiments were carried out for various conditions of air temperature (50 °C ≤ Tf ≤ 90 °C) and air velocity (2.5 m/s ≤ uf ≤ 4.5 m/s). From these data, a correlation for K was obtained and implemented in CFD simulations of the FB-2 equipment. The validation procedure showed an excellent agreement between the experimental and simulated data for the variation of the dimensionless moisture with time. Afterwards, in order to obtain a correlation for a range of conditions closer to those of the drying chute, a new dryer (GR-1) was designed and constructed. In this dryer, for an air temperature of 140 °C and an air velocity of 15 m/s, a drying time of about 6 s was required to reduce the iron ore moisture by two percentage points (wet basis). From experimental data collected in the GR-1, a correlation for K was obtained for another range of air temperatures (100 °C ≤ Tf ≤ 140 °C) and air velocities (5 m/s ≤ uf ≤ 15 m/s), implemented in CFD simulations of the GR-1 equipment and validated against the experimental data. Finally, CFD simulations of the drying chute equipment were performed using the correlation for K previously obtained in the GR-1. The CFD simulations of the drying chute involved a porous zone model to describe the sieve that composes the equipment. Physical coherence of the model was investigated and considered appropriate. The contours of velocity, temperature and humidity of both the fluid and solid phases were presented, as well as the regions in which the drying rate was higher. In addition, the impacts of closing some outlets of the equipment was evaluated using the simulator. Numerical results provided a better understanding of the operation in the drying chute and the simulator showed potential to evaluate possible improvements in its geometry and operation.